Creating relationship wellness : an introduction to the techniques of mindfulness for healthy relationships - Wijkstrom, Stephanie, 1982- (Universal Publishers, 2021)
"Mindfulness for your marriage is a tool book to be used by couples who want to gain the skill of relationship wellness, or those interested in deepening their understanding of what it means to nurture a loving relationship. Each chapter offers evidence-based, and therapist verified techniques to gain insight into yourself and your partners world. Mindfulness for your marriage offers a skills-based intervention that draws upon the fields of mindfulness and behavioral psychology, both recognized as pathways to enrichment. Each segment of this text builds upon the previous in an effort to lead the reader toward a mastery of relationship wellness"--